Professor adoece no trabalho : síndrome de Burnout, efeitos na ação pedagógica - Bottini, Maria Emília (2009)
At the present paper, we propose to search and go deeper into the studies regarding to Burnout Syndrome, through the identification and analysis of the syndrome s reflexes, which they are and how they interfere at the educational action. The teacher s work is a potentially stressful activity in which low salaries, little material and teaching resources, packed classrooms, tension in the relationship with students, excess of workload, unexpressive participation in the policies and institutional planning are some of the factors present at teacher s everyday life causing laborious stress and consequently Burnout Syndrome. This investigation was made with 37 teachers and 24 students, all of them from three municipal High Schools from Erechim City (RS Southern Brazil), totaling 61 people. A socialdemographic questionnaire and Maslach Burnout Inventory (MBI) were applied to the teachers; and an interview from an itinerary with notherly questions, to the students. The socialdemographic details are relevant to the understanding of Burnout Syndrome, once that some elements constitute explanations to this phenomenon which attacks teachers. The Maslach Burnout Inventory (MBI) results present high levels of emotional exhaustion, low level in personal fulfillment and decreasing of personality traits which suggest the existence of a sickly process in Burnout. In the interview, the students evidence (through their speeches) signs that they notice Burnout Syndrome reflexes in relation to teachers behavior- since these teachers have been annoyed, tired, and they have showed prejudicial and disrespectful attitudes with students during schooldays